Hubungan Pola Makan Dan Stress Dengan Kejadian Hipertensi Di Wilayah Kecamatan Tabunganen - ., Ernawati; Sri Purwanti Ariani (CV. ITTC INDONESIA, 2023)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in two measurements five minutes apart in a fairly calm/resting state. The incidence of hypertension in Central Kalimantan, Palangka Raya City for the age group >18 years is 93%, while the number of patients experiencing hypertension in the Tabunganen sub-district area from January-July 2022 is 112 people.To determine the relationship between diet and stress with the incidence of hypertension in the Tabunganen sub-district area.Correlational Analytical research type. The population in this study were patients experiencing hypertension. The sample consisted of 45 respondents. Correlation analysis uses the Spearman Rho test.There is a relationship between diet and physical activity and the incidence of hypertension with a correlation coefficient value for stress levels of 0.409 and a correlation coefficient for physical activity of 0.691 with a calculated p value of 0.001 < 0.05. This value shows that the hypotheses Ha1 and Ha2 are accepted, which means there is a relationship between the patterns. eating and physical activity with the incidence of hypertension. Health workers can strengthen health promotion efforts related to hypertension based on diet and physical activity and health workers carry out nursing care, especially for patients with hypertension and high risk related to diet and physical activity.